Pre Cal

simplify the quotient: [(x+1)^3(4x-9)-(16x+9)(x+1)^2]/[(x-6)(x+1)^3]

  1. 👍 0
  2. 👎 0
  3. 👁 91
asked by Angela
  1. = (x+1)^2[(x+1)(4x-9) - (16x+9)]/[(x-6)(x+1)^2]
    expand the square bracket and factor the result...
    = (x+1)^(4x+3)(x-6)/(x-6)(x+1)^2]
    = (4x+3)/(x+1) , x ≠ -1, 6

    1. 👍 0
    2. 👎 0
    posted by Reiny

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    I sent this in a little while back but the file got corrupted and I have to re do it and I forgot the answer please if it is not done today I fail the year. Simplify the polynomial 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A:31x^2 + 16x +

    asked by Random on June 6, 2016
  2. Algebra

    There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8

    asked by Juri on July 23, 2007
  3. algebra

    Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this? 16x-4y=20 -4x+y=-4 ___________ 16x-4y=20 (4)(-4x+y=-4)

    asked by struggling on May 26, 2007
  4. math

    Please check my answers! Simplify the product. 7x(x+4) A. 7x^2+4 B. 7x^2+28x

    asked by Sage on February 25, 2016
  5. Intermediate Algebra

    Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2 16x^2 - 2x + 5x^2 - 3x/2x^2 =21x^2 - 5/2x^2 Find the LCD 6/7z- 28, 8/x^2 -4x = 7x(x-4) Simplify 3x^2 - 2x/15x-10 = x/5 Let's start by looking at

    asked by Richard on November 3, 2006
  6. Math

    find any stationary points of the function g(x) = (2x-3)square root of 5+16x-4x^2 (0 less than or equal to x less than or equal to 4) and use the first derivative test to classify each stationary point as a local maximum or local

    asked by Pd on September 14, 2010
  7. Math

    5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10 - x + 3 = -16x - 20 +13 Group like terms. -16x - 7 = -16x - 7 Add 16x + 7 to both sides and write the equation as follows 0 = 0

    asked by Andrew on January 30, 2012
  8. Pre-Algebra

    1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A. 31x^2 + 16x + 1 B. x^2 - 12x + 1 **** C. x^2 + 16x + 1 D. x^2 + 16x + 2 2. 2x^2 + 8 - 4x + 3x - 6x^2 + 7 A. -8x^2 - 7x + 15 B. -4x^2 - x + 15 **** C. 4x^2 + x + 15 D. 8x^2 + 7x + 15 3. 4x^2 +

    asked by Help ASAP on May 10, 2018
  9. Math

    1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x a. 31x^2 + 16x + 1 b. x^2 - 12x + 1 c. x^2 + 16x + 1* d. x^2 + 16x + 2 2. 3x^2 + 6 - 2x + 5x - 4^2 + 9 a. -x^2 + 3x + 15* b. 7x^2 + 3x + 3 c. x^2 - 3x + 15 d. -x^2 + 7x + 15 3. 2x^2 + 6x - 7x +

    asked by Mynameisntyourbuisness on June 2, 2017
  10. math-algebra

    Simplify: [(4x^3y)(4^2xy)^-1]/(4xy^2) A. x /16y^2 B. 16x/y^2 C. x^2/16y D. y/16x^2

    asked by Anonymous on September 26, 2007

More Similar Questions